Pengaruh Intellectual Capital dan Corporate Governance Terhadap Kinerja Keuangan Perbankan di Indonesia - Tia Rizna Pratiwi (Jurnal Akuntansi dan Keuangan, 2017)
This study is aimed to investigate the impact of intellectual capital andcorporate governance on bank’s financial performance in Indonesia. Intellectualcapital is measured by Value Added Intellectual Coefficient(VAIC) method, while corporate governance is measured by corporate governance composit valueof Banks. The result indicates VACA and VAHU have influence on bank’sperformance in Indonesia which proxied by ROE and ROA.